Ethics of Using Artificial Intelligence in Islamic Education - Muhammad Yusuf Qona'ah; Abhirup Sarkar (Educatia : Jurnal Pendidikan dan Agama Islam, 2026)
This article provides a comprehensive ethical analysis of the use of Artificial Intelligence (AI) in Islamic education. AI technologies such as ChatGPT, personalized learning algorithms, automated assessment systems, and learning analytics have entered Islamic schools (madrasas) and pesantren, offering both opportunities and moral challenges. This study aims to: (1) identify the main ethical challenges of AI from an Islamic perspective; (2) formulate ethical principles derived from the Quran, Hadith, and maqashid al-shariah; (3) offer practical implementation scenarios. The research uses a qualitative library research method, analyzing international and national literature published in the last five years (2021-2026). Data analysis employs thematic content analysis. Findings reveal six core ethical challenges: opacity of algorithms, algorithmic bias, data privacy, diminished teacher authority, commodification of knowledge, and unequal access.In response, six corresponding Islamic ethical principles are developed: transparency (al-shafafiyyah), justice (al-adl), responsibility (al-masuliyyah), privacy (al-khusushiyyah), human autonomy (al-istiklaliyyah al-bashariyyah), and social solidarity (al-taawun). These principles are operationalized through three case studies: AI chatbots in pesantren, AI-based student grouping systems, and automated Quranic pronunciation assessment. The article concludes that AI can be integrated into Islamic education if guided by these principles, with the teacher remaining the ultimate moral and pedagogical authority.